2018
DOI: 10.1186/s13293-018-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-associated differences in mitochondrial function in human peripheral blood mononuclear cells (PBMCs) and brain

Abstract: BackgroundAlzheimer’s disease (AD) is the most common form of dementia, and it affects more women than men. Mitochondrial dysfunction (MD) plays a key role in AD, and it is detectable at an early stage of the degenerative process in peripheral tissues, such as peripheral mononuclear blood cells (PBMCs). However, whether these changes are also reflected in cerebral energy metabolism and whether sex-specific differences in mitochondrial function occur are not clear. Therefore, we estimated the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
64
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 63 publications
15
64
2
1
Order By: Relevance
“…For instance, here PBMCs were isolated from pooled peripheral blood from term equivalent male and female rats, limiting the ability to elucidate differences between individual animals and between male and female rat pups. Evidence from studies examining PBMCs isolated from adult humans suggests that sex differences in stimulated PBMC properties and secretion exist ( 105 107 ). While sex differences in secretion of PBMCs isolated at neonatal time points are not well-defined ( 35 , 37 ), evidence exists demonstrating sex-specific differences in brain inflammation following circulating myeloid cells depletion in neonatal mice ( 108 ) and that inflammatory responses following immune cell activation in the immature brain differ between males and females, as reviewed by Mallard et al ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, here PBMCs were isolated from pooled peripheral blood from term equivalent male and female rats, limiting the ability to elucidate differences between individual animals and between male and female rat pups. Evidence from studies examining PBMCs isolated from adult humans suggests that sex differences in stimulated PBMC properties and secretion exist ( 105 107 ). While sex differences in secretion of PBMCs isolated at neonatal time points are not well-defined ( 35 , 37 ), evidence exists demonstrating sex-specific differences in brain inflammation following circulating myeloid cells depletion in neonatal mice ( 108 ) and that inflammatory responses following immune cell activation in the immature brain differ between males and females, as reviewed by Mallard et al ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are few studies examining sex differences in tNAA one recent study reported similar results. Silaidos et al (2018) examined NAA as a proxy for mitochondrial dysfunction. There they found that female participants had higher NAA levels in both gray and white matter than male participants did; a similar finding to that reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The level of mitochondrial hemoglobin in the neurons is reduced in subjects who develop PD [ 31 ]. The localization of hemoglobin in the mitochondrial compartment could represent a protective mechanism in circulating leukocytes and neurons [ 32 ]. Indeed, the different hemoglobin modulation between cytosol and mitochondria could be the consequence of the different bioavailability of oxygen between the two genders; females are more predisposed to anemia and are physiologically lower iron levels than males, and this could play an important role in neurodegeneration [ 30 , 33 ].…”
Section: General Mechanisms Involved In Gender Differences In Parkmentioning
confidence: 99%